Features of accounting for labor cost - Kondratiuk, O.; Mykulskyi, V. (Літограф, 2017)
Accounting for labor costs is one of the most important and complex areas of accounting work, whose effective implementation requires timely, accurate and complete information.
Keywords: accounting for labor; accounting work; payroll is